Einige Bemerkungen über die Integralen vom Cauchy-Stieltjesschen Typus - Chavinson, S. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. Я. Хавинсон. Несколько замечаний об интегралах типа Коши-Стильтьеса S. Chavinson. Kai kurios pastabos apie Koši-Stiltieso tipo integralus